Complex Implant-Prosthetic Rehabilitation Following Sports Trauma with 14 Years of Follow-Up: Case Report - Alberto Murri dello Diago; Roberto Apponi; Vittorio Colombini; Lorenzo Mordini; Francesca Ideo (MDPI AG, 2021)
Tooth loss after traumatic dental injuries (TDI) often requires rehabilitation with a multidisciplinary treatment plan. In growing patients, the therapeutic approach may be different than in adults; the scientific literature offers alternative solutions even if they involve long, complex and uncomfortable treatments. Among the possible therapeutic options, implant-prosthetic treatment through the use of mini-implants is presented in this complex case report with a 14-year follow-up.